Management of Malignant Adenomas - Hall, Jason F. (Clinics in Colon and Rectal Surgery, 2015)
Most polyps that originate in the colon and rectum are benign. A small subset of polyps will contain a malignancy. Although most malignant adenomas are managed with colonic resection a number can be approached with endoscopic, minimally invasive, and observational techniques. This article reviews the histologic characteristics and adverse risk factors that would portend a poor oncologic outcome and therefore suggest formal colonic resection. Modern endoscopic techniques such as endoscopic mucosal resection and endoscopic submucosal resection are discussed.
Keywords: malignancy; adenoma; Haggitt criteria; endoscopic submucosal resection; endoscopic mucosal resection; polypectomy